The mythology of Mexico and Central America - Bierhorst, John. (New York W. Morrow, 1990)
Discusses the mythology from Indians of various regions of Mexico and Central America, describing origins, comparing the similar tales, and presenting some of the myths themselves.
Includes bibliographical references (p. 208-233) and index.
Keywords: Indian mythology -- Mexico; Indian mythology -- Central America; Indians of Mexico -- Folklore; Indians of Central America -- Folklore; Indians of Mexico -- Religion; Indians of Central America -- Religion